2022
DOI: 10.1007/s00590-022-03356-2
|View full text |Cite
|
Sign up to set email alerts
|

Autologous microfragmented adipose tissue and leukocyte-poor platelet-rich plasma combined with hyaluronic acid show comparable clinical outcomes for symptomatic early knee osteoarthritis over a two-year follow-up period: a prospective randomized clinical trial

Abstract: Purpose The purpose of this prospective randomized clinical trial is to compare the clinical outcomes of three injections of leucocyte-poor platelet-rich plasma (LP-PRP) and hyaluronic acid (HA) to a single dose of autologous microfragmented adipose tissue (AMAT) in patients with mild osteoarthritis at a two-year follow-up. Methods Eighty symptomatic knees in fifty patients (mean age: 62.38 ± 11.88 years) with Kellgren-Lawrence grade 0 to 2 osteoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
(61 reference statements)
2
15
0
Order By: Relevance
“…Gobbi et al performed a Randomized Clinical Trial comparing MAT with leukocyte-poor platelet-rich plasma plus hyaluronic acid with a 2 years follow-up. They showed that both treatments lead to significant clinical improvement without a relevant difference between each other within a cohort of patients with KL grades 1-2 [40] with an improvement in KOOS score in line with the results of this research.…”
Section: Discussionsupporting
confidence: 85%
“…Gobbi et al performed a Randomized Clinical Trial comparing MAT with leukocyte-poor platelet-rich plasma plus hyaluronic acid with a 2 years follow-up. They showed that both treatments lead to significant clinical improvement without a relevant difference between each other within a cohort of patients with KL grades 1-2 [40] with an improvement in KOOS score in line with the results of this research.…”
Section: Discussionsupporting
confidence: 85%
“…Patients lost at the final follow-up were 51 for MM-AT and 23 for control groups. Thirteen studies injected MM-AT bilaterally in some patients [ 30 , 32 , 33 , 35 , 36 , 37 , 38 , 41 , 43 , 45 , 46 , 47 , 53 , 54 , 56 , 58 ] and, among them, in one study the treatment was bilateral in all patients [ 58 ]. The ratio between males and females was 1.0 in the MM-AT group and 1.4 for the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…The mean BMI went from 24.7 [ 50 ] to > 35 [ 40 ] for MM-AT and from 26.0 [ 42 ] to 31.0 [ 29 ] for the control groups (12 studies did not report BMI). Patients presented different OA grades, often measured with KL classification: nine studies on KL 1–4 [ 28 , 29 , 39 , 44 , 45 , 46 , 54 , 56 , 59 ], eight studies on KL 3–4 [ 30 , 33 , 35 , 40 , 41 , 47 , 48 , 55 ], three studies on KL 2–3 [ 34 , 42 , 50 ], three studies on KL 1–3 [ 34 , 44 , 51 ], two studies on KL 1–2 [ 32 , 37 ], and two studies on KL 2–4 [ 36 , 53 ]. In addition, patients with mild, moderate, or severe OA grade [ 43 ], ICRS grade of 2–4 [ 51 , 52 ], and American College of Rheumatology criteria 1–3 [ 57 ] were also evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been shown in literature. In multi-centric, international, open-label study evaluating the outcomes of MFAT injections in patients with knee OA at 2-year follow-up significant functional and quality of life improvement was seen in 88% of patients [23]. In a prospective randomized control trial comparing leukocyte-poor PRP combined with HA and MFAT no significant superiority was seen for either group, both procedures were found to be safe with no major complications showing good results at mid-term follow-up [24].…”
Section: Adipose Stem Cellsmentioning
confidence: 99%